Zygomatic Implants: A Review - Sanchari Sinha Roy1 , Subrat Kumar Padhiary2 , Satyabrata Patnaik2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Zygoma implants (or zygomatic implants) vary from traditional dental implants in that they attach in ratherthan maxilla (upper jaw) in the zygomatic bone (cheekbone). They can be used where the consistency orquantity of maxillary bone is insufficient for normal dental implant placement. Inadequate maxillary bonevolume can be due to bone resorption as well as maxillary sinus pneumatization or a mixture of both. Therequired bone height for typical implant placement in the upper jaw posterior area should be approximately10 mm to ensure appropriate implant survival. Where there is inadequate bone available, bone graftingprocedures and sinus raising procedures should be done to increase bone volume. Procedures for bonegrafting in the jaws have the downside of extended care, limiting denture wear, the morbidity of donorsurgical site & graft rejection.